2008
DOI: 10.1111/j.1464-410x.2008.07902.x
|View full text |Cite
|
Sign up to set email alerts
|

Penile fracture: preoperative evaluation and surgical technique for optimal patient outcome

Abstract: OBJECTIVE To review the preoperative diagnostic evaluation and surgical treatment of penile fracture, as the condition is a urological emergency that requires immediate surgical exploration and repair. PATIENTS AND METHODS Between January 2003 and October 2007 eight patients presented to the emergency department with penile fracture after sexual intercourse. The clinical presentation, preoperative evaluation and imaging, surgical technique, and postoperative care were assessed to determine the optimal patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
111
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(122 citation statements)
references
References 11 publications
3
111
0
5
Order By: Relevance
“…On long term, 6.6% of patients in our series had ED, which is within the range of 0-16.6% previously reported. [13][14][15][16][17][18][19] We preferred the sub-coronal circumferential incision because of the excellent exposure of the three corpora, which avoids accidental missing of a urethral injury or multiple injuries of the tunica. 26 The right side was commonly affected (56.1%) in agreement with many reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On long term, 6.6% of patients in our series had ED, which is within the range of 0-16.6% previously reported. [13][14][15][16][17][18][19] We preferred the sub-coronal circumferential incision because of the excellent exposure of the three corpora, which avoids accidental missing of a urethral injury or multiple injuries of the tunica. 26 The right side was commonly affected (56.1%) in agreement with many reports.…”
Section: Discussionmentioning
confidence: 99%
“…11,13 Contemporary series showed that the incidence of ED after surgical repair of fracture penis ranges from 0% up to 16.6%. 6,7,[13][14][15][16][17][18][19] Several important issues may be raised during discussing the development of ED after surgical repair of fracture penis. First, is delayed presentation after trauma a risk factor for ED?…”
Section: Introductionmentioning
confidence: 99%
“…Kamdar et al [16], have suggested Citation: Rajendra Management involves prompt exploration and surgical repair of penile fractures (Figures 3,4) as reported in several contemporary publications [18]. Immediate surgical reconstruction results in faster recovery, decreased morbidity, lower complication rates, and lower incidence of long-term penile curvature [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…These are the degloving method with the degloving incision/circumcision incision and the ventral midline incision method (2). While postoperative complications have been reported to be higher with the ventral midline incision in the literature, no statistically significant difference was found (6).…”
Section: Discussionmentioning
confidence: 99%
“…In rare cases of uncertainty, radiological imaging methods are also used. These methods are magnetic resonance imaging (MRI), ultrasonography (US), cavernosography and urethrography (2). When penile fracture case reports are examined, penile trauma was found to be more common in Middle East and North Africa when compared to the rest of the world (3).…”
Section: Introductionmentioning
confidence: 99%